Effect of Chemical Enhancing-Technology on the Properties of Recycled Aggregate. (31st July 2020) - Li, Ping; Zhang, Dongmei; Wei, Di; Xiong, Jianping; Li, Jing
Abstract : Strengthening the attached old cement mortar of recycled aggregate (RA) is a common approach to enhance the RA properties. In this study, four representative chemical enhancing-technologies were chosen. Through the analysis of physical properties, mechanical properties, and shape indexes, the changes of performance before and after strengthening were tested, so as to grasp the influence of chemical enhancing-technologies on the performance of RA. The results indicated that the chemical strengthening methods had obvious influence on the physical properties of RA, such as density and water absorption. Due to the different chemical enhancing mechanism, the influence trend and range were varied. The mechanical properties of RA such as crushing value and abrasion value were obviously improved by chemical enhancement. However, chemical enhancement had an effect on the shape of RA, which will slightly reduce the angularity index and sphericity index. The texture index of RA with C-3 and C-7 decreased sharply, but texture index increased after abrasion, and the discrepancy of aggregate texture index of different enhancing methods is significantly reduced. The microanalysis exhibited that the aggregate surface structure with C-3 and H was large, but there were a lot of fine structures on the aggregate surface with C-7 and N-P. Different chemical enhancing methods have different effects on the mechanical performance and microstructure of RA, but it should be noted that the fluctuation of RA performance tends to increase.